PENGARUH LINGKUNGAN KELUARGA TERHADAP KEINGINAN SISWA/I KELAS XII IPA SMA NEGERI 1 PANOMBEIAN PANEI UNTUK MELANJUTKAN PENDIDIKAN KEPERGURUAN TINGGI - Deasy Vita Yessikha Nainggolan (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
The advancement of a nation is determined by the quality of its human resources that becomes the key for the advancement through education. One of the efforts to develop capability in human beings is through education in stages which is influenced by families. A family will motivate to study and to continue studying at the universities. The objective of the research is to find out the effects of family on the interesr of grade XII IPA students of SMA Negeri (Public Senior High School) I Panombeian Panei in continuing their study to the university level, measured with the indicators such as the way parents educate, relationship among family members, family atmosphere, and economic condition. The variable of family is an independent variable, and the variable of interest is a dependent variable. A sample size of 100 students serves as the respondents, in 2022. The result of the hypothetical test shows that family has positive and significant effects on the interest of the respondents in continuing their study to the university level at p-value=0.00 < 0.05. The result of determination coefficient test showed that R2 = 0.864 which indicated that the respondent’s interest in continuing their study to the university level was 86.4% influenced by their families while the remaining 16.6% was influenced by other factors excluded from this research.